THE REVIEW OF LEADERSHIP STYLE, EMPLOYEE PROMOTION, AND MOTIVATION - Kurniawanto, Hari; Moeins, Anoesyirwan; Herwanto, Djoko (Dinasti International Journal of Digital Business Management, 2021)
This research is conducted to obtain various gathered to be data analyzes and interpretations so that we can get a picture concerning the influence of leadership on the execution of officer promotion and its implication to officer motivation. The research method used is the descriptive survey method and survey of explanatory. The sample size is 100 officer people. The unit analyzes in this research is cross-sectional. The result of this research is leadership in PT. Telkom Kandatel South Jakarta in general goodness. The Officer promotion in PT. Telkom Kandatel South Jakarta, in general, is good enough. The administration affects officer promotion, the administration has an impact on officer motivation, and advertising affects officer motivation.